2022
DOI: 10.1063/5.0078823
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of dielectric barrier discharge plasma device and plasma jet to generate plasma activated water and post-discharge trapping of reactive species

Abstract: This work shows a comparative study of a change in properties of plasma-activated water (PAW) when prepared by using two different dielectric barrier discharge (DBD) configurations named a pencil plasma jet (PPJ) and a plasma device (PD). The air plasma produced from the DBD-PPJ and DBD-PD is characterized by voltage-current characteristics, and plasma species/radicals are identified using optical emission spectroscopy. Moreover, the present work emphasizes the trapping of reactive species (O3, NOx, etc.) carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The variation in pH and oxidizing potential (oxidation-reduction potential, ORP) of water with increasing plasma treatment time is shown in figure 4 (47), and also observed in our past published literature (19,48).…”
Section: Determination Of Reactive Species and Physicochemical Proper...supporting
confidence: 75%
See 1 more Smart Citation
“…The variation in pH and oxidizing potential (oxidation-reduction potential, ORP) of water with increasing plasma treatment time is shown in figure 4 (47), and also observed in our past published literature (19,48).…”
Section: Determination Of Reactive Species and Physicochemical Proper...supporting
confidence: 75%
“…The various reactive species such as hydroxyl radical (HO•), dissolved ozone (O 3 ), peroxynitrite (ONOO‾), nitric oxide (NO), etc. are responsible for degraded antibiotics present in wastewater (13)(14)(15)(16)(17)(18)(19)(20)(21). Rong et al (13) reported the role of HO• in degradation of sulfadiazine antibiotics in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The air plasma optical emission spectra is shown in Figure 1 (see supplementary Figure S3 for details of emission lines) (44,(47)(48)(49)(50). These generated species/radicals are the major contributors that change the physicochemical properties of the solution as well as responsible for degradation of organic impurities present in wastewater.…”
Section: Plasma Characterizationmentioning
confidence: 99%
“…To identify the species formed during plasma-dye solution interaction, the air plasma was treated with ultrapure milli-Q water. The change in physicochemical properties (pH, oxidation-reduction potential (ORP), total dissolved solids (TDS), and electrical conductivity (EC)) and formation of reactive species (nitrate ions (NO 3 ˉ), nitrite ions (NO 2 ˉ), hydrogen peroxide (H 2 O 2 ), and dissolved ozone (O 3 )) in water were measured periodically by following the procedure mentioned in our earlier reported work (35,41,42).…”
Section: Zeroth Order Modelmentioning
confidence: 99%
“…The above degradation of dyes solution with plasma solution occurs due to the formation of various reactive species in dye solution (35,41,42,46). These species were responsible for the degradation and mineralization of the above-mentioned dyes.…”
Section: Physicochemical Properties and Reactive Oxygen-nitrogen Spec...mentioning
confidence: 99%